Microstructure evolution and grain refinement mechanism of rapidly solidified single-phase copper based alloys. (20th November 2022) - Xu, Xiaolong; Tang, Cheng; Wang, Hongfu; An, Yukang; Zhao, Yuhong
Highlights: The maximum undercoolings were achieved respectively by using the deep undercooling technology. The recalescence behavior and microstructure refinement were systematically studied. The relationship between solute composition and solidification process was established. High-angle grain boundaries and twin boundaries exist in the microstructure at high undercooling. Abstract: The Cu65Ni35, Cu60Ni40 and Cu55Ni45 alloys were undercooled by fluxing method, and the rapid solidification structure with different undercoolings were also obtained. At the same time, the interface migration process during rapid solidification was photographed by high-speed photography, and the relationship between the morphological characteristics of solidification front and undercooling was analyzed. The microstructures of the three alloys were observed by metallographic microscope, and the microstructure characteristics and evolution law were systematically studied. It was found that two grain refinement events occurred in the low undercooling range and high undercooling range, respectively. The EBSD test of grain refined microstructures showed that the microstructure in the low undercooling range has a high proportion of low-angle grain boundaries and high strength textures. However, there were a large proportion of high-angle grain boundaries and a high proportion of twin grain boundaries and more randomly oriented grains in the microstructure in the high undercooling range. The TEM test of the Cu55Ni45 alloy with the maximum undercooling of 284 K showed that there were high-density dislocation networks and stacking faults in the grains. Finally, the evolution relationship between microstructure hardness and undercooling was systematically studied. It was found that the microhardness of the three alloys decreased sharply near the critical undercooling. Combined with EBSD, TEM and microhardness analysis, it was confirmed that the grain refinement under low undercooling was caused by dendrite remelting, while the grain refinement under high undercooling was caused by stress-induced recrystallization. Graphical abstract: Image, graphical abstract